Typology and human impact in Kouris river watershed (Cyprus), using GIS according to 2000/60 directive for water protection - Ηλιάδης, Μ.; Οικονομίδης, Δ.; Αλμπανάκης, Κ.; Βουβαλίδης, Κ. (Bulletin of the Geological Society of Greece, 2011)
This paper was based on some of the key provisions of Directive 2000/60, which are intended to establish a framework for water protection. Senior environmental objective of Directive 2000/60 is to achieve good status for all waters by 2015. To achieve this goal, some steps followed as required by the Directive. This work was originally to determine the watershed of the river Kouris, which is the study area, located west of Limassol city (Cyprus), in an area calculated about 357km2. The main features of the river basin are indicated, such as the climatic data, geology, agriculture and livestock and also the human interventions relating to the construction of the Kouris dam and river diversion tunnel Diarizos. Additionally, there is a classification of land cover, according to the Corine land cover 2006. A description is made too, for the protected areas, covered in the study area. An application of the typology, is made, to identify the types and the water bodies as defined by the Directive 2000/60. Of the two systems which it lays down (A and B), the system B is selected because is more flexible than the system A and allows the use of additional descriptors. Due to the construction of the Kouris dam, of the impoundment of water upstream and of the absence of feeder in the downstream region, the river basin of Kouris is divided finally into two independent river basins. So it seems appropriate to apply a typology for the watershed of Kouris River in its natural state and one for the two independent river basins, which are resulting from the construction of the dam. Also two typologies are applied, for the descriptors. In one case as descriptors are selected, the altitude, the size of the river basin, the geology, and as an optional descriptor, the gradients. In the second case the selected descriptors, as applied in Cyprus, are the flow regime (continuous or non-continuous) and the annual volume of rainfall resulting from the rainfall and the size of the river basin. The results obtained for the Kouris watershed in its natural state , are 8 types and 62 water bodies, in the case of four descriptors and 3 types and 53 water bodies, in the case of the descriptors like applied in Cyprus. According to the analysis, it is obvious that System B with the use of the four descriptors defines with more accuracy the water bodies than the one applied in Cyprus.